The Concept of Maqasid Sharia According to Jasser Auda - Andri Sutrisno (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
Maqasid Sharia is a very important theme in the discourse of Islamic thought in this contemporary era. In classical times, this science became part of the science of ushul fiqh, but in the present, it has stood alone as a scientific discipline in Islam. This can be seen in the contribution of thought made by Jasser Auda to make the science of maqasid Sharia a form of a principle, higher intents, and basic values of Sharia in the context of a movement to answer a problem of the times that have changed from time to time. This is done to make maqasid Sharia a form of reform of a new paradigm and ijtihad so that Islam becomes a religion that is always high, and there is no other religion higher than Islam. For that, in this study. Researchers use a descriptive qualitative approach with the type of literature research. Where in the process of collecting data, researchers conduct research by reading and analyzing Jasser auda books and several books, and journal articles to support outlining data on the concept of maqasid sharia Jasser auda perspective. The conclusion of this study is that Jasser Auda is a Muslim intellectual born in Cairo, Egypt, and is currently Jasser Auda is the director and founder of the maqashid research center in London, England. His books discuss a lot about the science of maqasid Sharia to answer the problems of this contemporary era. That the epistemology of maqasid Sharia according to Jasser auda must have four meanings, namely wisdom behind a law, a good ultimate goal in formulating laws, having a goal to Allah Swt. as well as the purpose of moral concepts that are the basis for making laws, and providing a value as well as a principle of humanity in human life.